Зв’язок національної афіліації з національною ідентичністю української студентської молоді - Співак, Любов Миколаївна (Проблеми сучасної психології : ЗНУ, 2020)
Позитивна національна ідентичність молодих громадян держави підвищує стабільність кожної нації. Студентський вік є сенситивним для розвитку національної ідентичності. Мета статті – емпірично вивчити зв’язок національної афіліації з розвитком національної ідентичності українських студентів вітчизняних закладів вищої освіти. В емпіричному дослідженні застосовано модифіковану методику «Етнічна аффіліація» й методику оцінки позитивності та невизначеності етнічної ідентичності. Встановлено, що в найбільшої кількості студентів врівноважені особисті інтереси й націоафіліативні прагнення, в дещо меншої – особисті інтереси домінують над груповими, в найменшої – переважають націоафіліативні прагнення. Більшість студентів вирізняє високий рівень національної ідентичності, що засвідчує їхня національна гордість і чіткість усвідомлення свого націокультурного походження і національної належності в ситуаціях міжнаціональних взаємодій. У меншої кількості студентів помічено середній і низький рівні національної ідентичності, що виявляються в недостатній чіткості усвідомлення ними своєї національної належності та переживанні національної гордості в окремих ситуаціях міжнаціональних взаємодій. Визначено статистично сильний і додатній (прямий) зв’язок між національною афіліацією і позитивністю національної ідентичності студентів. Досліджувані з домінуючими націоафіліативними прагненнями пишаються своїм націокультурним походженням і національною належністю майже в кожній ситуації міжнаціональних взаємодій; із врівноваженими націоафіліативними прагненнями й особистими інтересами – майже в половині таких ситуацій; з переважаючими особистими інтересами над груповими – лише в окремих ситуаціях. Зафіксовано статистично сильний і від’ємний (обернений) зв’язок між національною афіліацією і чіткістю національної ідентичності студентів. Досліджувані з домінуючими націоафіліативними прагненнями чіткіше усвідомлюють своє націокультурне походження і національну належність, порівняно зі студентами, в яких особисті інтереси переважають над груповими. Отож, емпірично доведено наявність статистично значущого зв’язку національної афіліації з національною ідентичністю українських студентів вітчизняних закладів вищої освіти
Relationship between national affiliation and national identity of ukrainian students youth
A positive national identity of young citizens of the state increases the stability of each nation. Student age is sensitive to the development of national identity. The purpose of the article is to empirically study the connection of the national affiliation with the development of the national identity of Ukrainian students of domestic higher education institutions. The empirical study used a modified method of “Ethnic Affiliation” and a method of assessing the positivity and uncertainty of ethnic identity. It is established that in the largest number of students personal interests and national affiliative aspirations are balanced, in a slightly smaller one – personal interests dominate over group ones, in the smallest – national affiliative aspirations prevail. Most students have a high level of national identity, which testifies to their national pride and clear awareness of their national and cultural origins and nationality in situations of interethnic interaction. A smaller number of students noticed medium and low levels of national identity, which is manifested in a lack of clarity in their awareness of their nationality and the experience of national pride in certain situations of interethnic interaction. A statistically strong and positive (direct) relationship between national affiliation and positivity of students’ national identity was identified. Researchers with dominant national affiliative aspirations are proud of their national and cultural origin and nationality in almost every situation of interethnic interaction; with balanced national affiliation aspirations and personal interests – in almost half of such situations; with predominant personal interests over group ones – only in certain situations. There is a statistically strong and negative (inverse) relationship between national affiliation and the clarity of students’ national identity. Researchers with dominant national affiliative aspirations are more aware of their national and cultural origins and national affiliation, compared with students in whom personal interests prevail over group ones. Thus, the existence of a statistically significant relationship of the national affiliation with the national identity of Ukrainian students of domestic higher education institutions has been empirically proved
Keywords: національна афіліація; національна ідентичність; нація; студент; заклади вищої освіти; national affiliation; national identity; nation; student; higher education institutions